Non-Typhoidal Salmonella and the Risk of Kawasaki Disease: A Nationwide Population-Based Cohort Study - Chen, Thomas Yen-Ting; Chou, Mei-Chia; Lai, Jung-Nien; Chiu, Lu-Ting; Chang, Renin; Hung, Yao-Min; Wei, James Cheng-Chung (Frontiers in Immunology, 2021)
Objective: The aim of this study was to investigate the relationship between non-typhoidal Salmonella (NTS) infection and the risk of Kawasaki disease (KD) by using a nationwide population-based data set in Taiwan. Methods: In this retrospective cohort study, we enrolled 69,116 patients under 18 years of age, with NTS from January 1st, 2000, to December 31st, 2013, using the population-based National Health Insurance Research Database of Taiwan. A comparison group without NTS was matched (at a 1:4 ratio) by propensity score. The two cohorts were followed from the initial diagnosis of NTS until the date of KD development or December 31, 2013. Cox proportional hazard regression analysis was conducted to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) after adjusting for covariates. Also, we conducted sensitivity analyses to examine our findings. Results: After adjusting for covariates, the risk of KD for the children with NTS was significantly higher than that of the comparison group (hazard ratio = 1.31; 95% confidence interval = 1.03-1.66; p < 0.01). Stratified analysis showed that the associated risk of the investigated outcome was significant in children aged ≤2 years (aHR= 1.31, 95% C.I. 1.02-1.69), in female patients (aHR= 1.46, 95% C.I. 1.03-2.08), and in those without allergic diseases. Conclusions: NTS is associated with an increased risk of KD in Taiwanese children.